Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.bbalip.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome deficiency-induced ER stress and SREBP-2 pathway activation in the liver of newborn PEX2 knock-out mice

Abstract: Disruption of the Pex2 gene leads to peroxisome deficiency and widespread metabolic dysfunction. We previously demonstrated that peroxisomes are critical for maintaining cholesterol homeostasis, using peroxisome-deficient Pex2−/− mice on a hybrid Swiss Webster×129S6/SvEv (SW/129) genetic background. Peroxisome deficiency activates hepatic endoplasmic reticulum (ER) stress pathways, leading to dysregulation of the endogenous sterol response mechanism. Herein, we demonstrate a more profound dysregulation of chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 66 publications
(109 reference statements)
5
33
3
Order By: Relevance
“…Changes in the fatty acid profile of Vhl À/À /Hif1a À/À livers were similar as in Vhl À/À livers ( Figure 2G; Table S2). Importantly, fatty acid profiles from Vhl À/À and Vhl À/À /Hif1a À/À livers were comparable to P13 peroxisomedeficient Pex2 À/À livers that also displayed steatosis ( Figure S4A) (Keane et al, 2007;Kovacs et al, 2012).…”
Section: Changes In Lipid Composition In Vhl -/-Livers Are Reminiscenmentioning
confidence: 88%
“…Changes in the fatty acid profile of Vhl À/À /Hif1a À/À livers were similar as in Vhl À/À livers ( Figure 2G; Table S2). Importantly, fatty acid profiles from Vhl À/À and Vhl À/À /Hif1a À/À livers were comparable to P13 peroxisomedeficient Pex2 À/À livers that also displayed steatosis ( Figure S4A) (Keane et al, 2007;Kovacs et al, 2012).…”
Section: Changes In Lipid Composition In Vhl -/-Livers Are Reminiscenmentioning
confidence: 88%
“…These changes closely follow the loss of functional peroxisomes in time, illustrating the dependence of other cellular compartments on intact peroxisomes [81,82]. Mitochondria are affected at several levels, including the mtDNA, the activity of the respiratory complexes and the structure of the inner membrane whereas matrix function is preserved or even increased [21,83].…”
Section: Mitochondrial Anomalies In Murine Hepatocytes Lacking Functimentioning
confidence: 97%
“…It was also shown that the ER compartment is enlarged in peroxisome deficient hepatocytes and mediators of ER stress signaling pathways (PERK, ATF4) are upregulated [80][81][82]. It was suggested that these ER perturbations deregulate SREBP signaling and cholesterol homeostasis [82].…”
Section: Other Cellular Adaptations In Murine Pex5 Deficient Hepatocytesmentioning
confidence: 98%
See 1 more Smart Citation
“…Indirect consequences of reduced peroxisomal metabolism like activation of ER stress pathways and mitochondrial dysfunction might also contribute to alterations in lipid metabolism Kovacs et al, 2009Kovacs et al, , 2012. Toxic effects of accumulation of peroxisomal β-oxidation substrates might damage the mitochondrial compartment by altering the lipid composition of mitochondrial membranes.…”
Section: Metabolic Consequences Of Reduced Peroxisome Abundancementioning
confidence: 99%